Present status of Mute Swans Cygnus olor, Whooper Swans C. cygnus and Bewick's Swans C. bewickii in the Eastern Baltic Region - Kuresoo, Andres (Wildfowl, 2013)
Census work on wintering duck and swan populations has been undertaken in most European countries during recent decades as national projects but more especially as international counts promoted by the International Waterfowl and Wetlands Research Bureau (IWRB). Intensive January counts were conducted annually from 1967-89 in Estonia (Kuresoo 1985,1988), and in 1967-74 and 1984-89 in Latvia (Viksne & Stipniece 1988). In 1987-89 nationwide censuses were carried out in Lithunia (Raudonikis et al. 1989). Some data for 1988 are available also from the Kaliningrad Region of the Russian SFSR (Grishanov, unpubl.). Two swan species - the Mute Swan Cygnus olor and Whooper Swan Cygnus cygnus, winter regularly in this region; the Bewick’s Swan Cygnus columbianus bewickii, is a very rare wintering bird.